Health-related Quality of Life Instrument With 8 Items for Use in Patients With Type 2 Diabetes Mellitus: A Validation Study in Korea - Juyoung Kim; Hyeon-Jeong Lee; Min-Woo Jo (Korean Society for Preventive Medicine, 2022)
Objectives This study assessed the validity and reliability of the Health-related Quality of Life Instrument with 8 Items (HINT-8) in patients with diabetes. HINT-8 is a newly-developed, generic health-related quality of life (HRQoL) instrument. Methods Three HRQoL instruments-HINT-8, EuroQoL 5-Dimension 5-Level (EQ-5D-5L), and Short Form Health Survey version 2.0 (SF-36v2)-were provided to 300 patients with diabetes visiting a tertiary hospital for follow-up visits in Korea. The HRQoL scores obtained using the HINT-8 were evaluated for subgroups with known differences based on demographics and diabetes-related characteristics (known-group validity). The mean scores of the instruments were compared between groups segmented by their responses to the HINT-8 (discriminatory ability). Correlation coefficients of the HINT-8 with other instruments were calculated (convergent and divergent validity). The Cohen kappa and intra-class correlation coefficient (ICC) were also evaluated (test-retest reliability). Results The average HINT-8 indexes were lower among women, older, and less-educated subjects. Subjects who did not list any problems on the HINT-8 had significantly higher HRQoL scores than those who did. The correlation coefficients of the HINT-8 with the EQ-5D-5L index and EuroQoL visual analogue scale were 0.715 (p<0.001) and 0.517 (p<0.001), respectively. The correlation coefficients between the HINT-8 index and the scores of 8 domains of the SF-36v2 ranged from 0.478 (p<0.001) to 0.669 (p<0.001). The Cohen kappa values for the HINT-8 ranged from 0.268 to 0.601, and the ICC of the HINT-8 index was 0.800 (95% confidence interval [CI], 0.720 to 0.860). Conclusions This study showed that the HINT-8 is a valid and reliable HRQoL instrument for patients with diabetes.